Separated and integrated perspectives on environmental, economic, and social dimensions – an investigation of student views on sustainable development. Issue 8 (16th November 2016) - Berglund, Teresa; Gericke, Niklas
Abstract : The sustainable development (SD) concept is based on the idea that economic and social development should be linked to the environment. However, controversies about various associated issues often arise due to the differences in protagonists' viewpoints, depending partly on whether they focus mainly on environmental, economic, or social dimensions and partly on ideological stances related (for instance) to the optimal ways of promoting economic growth and social justice. This study investigates views of 638 Swedish upper secondary students who responded to a questionnaire probing their views of SD from two perspectives. In the first, the dimensions were separately introduced, so the respondents only had to consider one dimension at a time. In the second, the dimensions were introduced in an integrated fashion, so the respondents had to consider effects related to all three dimensions. The results strongly indicate that the students' views and priorities concerning the dimensions depend on both the perspective and the context. Implications for teaching and learning are discussed.